Exemption from criminal liability in connection with active repentance - Biebayeva, A.A.; Kalguzhinova А.М. (Bulletin of the Karaganda University “Law Series”, 2023)
The priority direction of improving the criminal legislation of the Republic of Kazakhstan is to ensure a balance of “punitive, restorative and preventive means of criminal law regulation”. The authors comprehensively investigated the content of the norm on exemption from criminal liability in connection with active repentance, which occupies a central place in the domestic concept of restorative justice. The study was conducted on the basis of the dialectical method of cognition of social processes, using formal legal, historical-legal, comparative-legal methods, the method of structural-system analysis. In the course of the study, the scientific works of Kazakh and Russian scientists, the current criminal legislation were studied. The main part of the article traces the history of the legal regulation of active repentance under the Criminal Code of the Kazakh SSR of 1959, the Criminal Code of the Republic of Kazakhstan of 1997 and 2014. The essence of active repentance is determined, the legal nature is revealed, the objective and subjective grounds and conditions fixed in the law are analyzed, the procedure for applying exemption from criminal liability in connection with active repentance is shown, the legal and social significance of this type of exemption from criminal liability is shown. The correlation of general and special norms providing for the possibility of exemption from criminal liability in connection with active repentance is carried out. The institutions of voluntary renunciation of a criminal offense and active repentance are differentiated. Based on the evaluation of the results of theoretical research and current legislation, conclusions are formulated regarding the incentive-stimulating potential of the norm on exemption from criminal liability in connection with active repentance.